A Complex Analysis of Labour Market in the European Union. Benefits and Barriers for Romania - Alin Ioan CREŢU; Laurentiu TESCAN (Revista de Management Comparat International)
The European Union aims, as the main objective, to increase the employment rate of the population and using it to its full potential in order to increase living standards. When control of barriers between EU Member States was lifted, it was necessary to create a european single market (Single European Market) that encouraged the interdependence of the economies of states and the development of a common system of laws. Taking into account the social component, single labor market (European Single Labour Market) is a critical element in achieving the benefits of an integrated market. Moreover, it is one of the key forces for achieving the Europe 2020 goals, particularly in relation to employment rates and initiative Youth on the Move (in order to improve education and employment among young people).